Integrating photovoltaic (Pv) solar cells and supercapacitors for sustainable energy devices: A review - Nordin N.A.; Ansari M.N.M.; Nomanbhay S.M.; Hamid N.A.; Tan N.M.L.; Yahya Z.; Abdullah I. (MDPI, 2023)
Capacitance; Electric batteries; Energy conservation; Energy storage; Fossil fuels; Hybrid systems; Life cycle; Solar cells; Solar energy; Solar power generation; Storage (materials); Thermoelectric equipment; Cost of energies; Energy generations; Green energy; Integrated device; Levelized cost of energy; Levelized costs; Miniaturisation; Photovoltaic solar cells; Power conversion efficiencies; Wearable devices; Supercapacitor